Multilayered Fluorine Doped SnO2 Inverse Opal/WO3/BiVO4 Film for Solar Water Oxidation: Systematic Development and Defined Role of Each Layer. Issue 15 (17th October 2019) - Yun, Gun; Arunachalam, Maheswari; Ahn, Kwang-Soon; Nam, Ki Min; Ha, Jun-Seok; Kang, Soon Hyung
Abstract : We developed the multilayered fluorine doped SnO2 (abbreviated as FTO) inverse opal (IO)/WO3 /BiVO4 film by sol-gel based spin coating, subsequently followed by facile electrodeposition. Above FTO IO template, both WO3 and BiVO4 layers were prepared by the electrodeposition methods in the variation of charge amount of 200–1, 000 mC cm −2 and of 300–1, 500 mC cm −2, respectively. On increasing the loaded charge amount of WO3 under the constant loaded amount of BiVO4, the light absorption in the near 400 nm is increased to steadily enhance PEC performance. In contrast, the further loaded WO3 layer of 800–1, 000 mC cm −2 on FTO IO film degrades PEC activity, due to the increase of the intrinsic material and interfacial resistances. Meanwhile, on increasing the electrodeposited charge amount of BiVO4 under the constant charge amount of WO3, the light absorption toward the visible wavelength is sharply increased, and gives rise to the enhancement of PEC performance; and conversely, the more loaded BiVO4 of 1, 200–1, 500 mC cm −2 induced the decay of PEC performance. The optimum condition in FTO IO/WO3 (600 mC cm −2 )/BiVO4 (600 mC cm −2 ) film was well established, and the function or role of each layer was confirmed using photoluminescence, charge separation/transfer efficiency, and photovoltage-time spectra.